Bribery, fraud, cheating: how to explain and to avoid organizational wrongdoing - Pohlmann, Markus; Dannecker, Gerhard; Valarini, Elizângela (Springer Fachmedien Wiesbaden, 2020)
The fight against organized crime -- Anti-corruption in Brazil -- Corruption issues and corporate compliance in China -- Manipulation of medical patient data in organ transplantation -- Overcoming the current system of corporate criminal law -- Systemic and preventive effects of the market economy.
Keywords: Konferenzschrift; Aufsatzsammlung; Organisiertes Verbrechen; Wirtschaftskriminalität